Wójtowa Góra w Sieciechowie - Reczulski, Łukasz (Acta Universitatis Lodziensis. Folia Archaeologica, 2017)
The history of Sieciechów and located monuments on its area for over 140 years are the subject of intensive research by historians, architectural historians and archaeologists. Particular attention is drawn primarily researchers station called Mountain village mayors – a small (now almost totally destroyed) hill situated west of the center of today’s settlement, considered by some researchers for the location of the well-known from written sources castrum Sieciech. This article discusses how far unpublished materials relating to this position, which is a collection of 399 pieces of pottery derived from within two archaeological sites located in the southern part Wójtowa Mountains. Analysis of these artifakts has allowed the protrusion of a new and different about the current interpretation of the functional position. Now, as a result of the analysis of these materials, and correlating the information obtained in this way with the data on the stratigraphy of the hill, the view of past defensive been denied a Wójtowa Mountains. In the light of the development of this material in position to function only of an open settlement, and the chronology based on the analysis of the ceramic material, can be determined by the age XIII, XIV or early age. Presumably, discussed the settlement was destroyed by the Tartar invasion.